Extra-Terrestrials or Terrestrial Heretics? Being Green in the Middle Ages - Gammie, Rosamund M. (Theology and science, 2024)
In this paper, we seek to propose a novel solution to the Green Children of Woolpit, a twelfth-century “alien” mystery by approaching the “otherworldly” through a terrestrial, theological lens. In focusing specifically on their otherworldliness, we suggest a congruence between the children's characteristics and the theological threat of early Catharism. When viewed Christologically, the Green Children mystery offers ample opportunity for exotheological discourse, focusing as it does on key Christian theological issues such as Christ's humanity, the Incarnation, and what it means to be human in the Middle Ages.